ESCATOLOGY OF GRAVE VISITATION AND ITS INFLUENCE ON SPIRITUALITY: A Study of Pilgrimage Participants in Pakondang Village, Rubaru, Sumenep, Madura - Bisyarotus Zakiyah; Rozinah AS (Living Sufism: Journal of Sufism and Psychotherapy, 2025)
Eschatology is one of the branches of philosophy that discusses human life after death. Meanwhile, visiting graves is not just about visiting someone's grave, but visiting graves is an activity of visiting the graves of relatives or pious people to pray for the deceased and taking lessons from them, and hoping for blessings from deceased who during their lifetime were pious people. This research discusses the dimensions of eschatology in visiting graves and the influence of eschatology on the spiritual values of the pilgrims. This research uses a qualitative field approach with data collection techniques in the form of interviews and participatory observations. The eschatology of visiting graves greatly influences the spiritual values of the pilgrims of the grave of Bhujuk Agung Bheleng, also known as Astah Abdul Karim in Pakondang Village, Rubaru Sumenep, both in terms of its influence on the values of faith, piety, and morality. This is marked by an increasing awareness of the temporality of life and the certainty of death. By remembering death, the pilgrims try as much as possible to increase their piety by multiplying good deeds and having noble character both toward Allah SWT, fellow humans, and other creatures.